PKM Peningkatan Pengetahuan Ibu dalam Pencegahan Stunting pada Balita - Fatmawati, Tina Yuli; Nurfitriani, Nurfitriani; Efni, Nel (Universitas Baiturrahim, 2024)
Currently, Indonesia is still facing nutritional problems that have a serious impact on the quality of human resources (HR). One of the problems of malnutrition that is still quite high in Indonesia is stunting and wasting in toddlers as well as anemia and chronic energy deficiency (KEK) in pregnant women. The purpose of this community service is to increase mothers' knowledge about stunting including: understanding, causes, impacts, prevention and treatment of stunting. Methods of community service through lectures, discussions, and anthropometric examination of children. Community service activities are carried out in Legok Village. The series of activities were carried out from March to August 2023. The target of the dedication was 20 mothers. The result of this service is an increase in mother's knowledge in preventing stunting. It is suggested that the Cadres are expected to be active in assisting the Community Health Centers in running an extension program regarding 1000 HPK as an effort to prevent stunting. Counseling participants should always pay attention to their children's growth and development so as to avoid the problem of stunting which will have an impact on decreasing the child's health status